Asymmetries in swimming: Where do they come from? - Sanders, R. H.; Thow, J.; Fairweather, M. M. (Journal of Swimming Research, 2011)
This paper reviews the etiology of asymmetries in swimming. A model of factors related to asymmetries was used as a basis for discussion of the etiology of asymmetries among swimmers. Asymmetries can include bilateralasymmetries and muscle imbalances leading to postural changes. The link between asymmetriesand swimming performance is highlighted throughout.